Relative stability, performance, and superiority of crop genotypes across environments - Kamidi, R.E. (2001)
Assessments of the stability as well as the performance of plant genotypes across diverse environmental conditions are important to plant breeders and agronomists as tools for selecting superior cultivars for the target environments. In this study, the shortcomings of fitted response as an indicator of relative stability are discussed and use of a genotype environment correlation coefficient, rge, as a measure of relative stability is proposed. Two other relevant indices are introduced: performance index, pi, and superiority index, si. The latter is a compound index for stability and performance that provides a simple method for selecting superior genotypes for relevant environments. In application, a distinction is made between specific stability (over space and microclimate) and general stability (over space and time) depending on the format of the specified environmental index. A statistical significance test for relative stability is considered and three datasets are used to demonstrate the application of derived indices under varying environment combinations. Appraisal of the method and some currently appealing procedures applied to the same dataset reveal a general concordance under similar conditions. The introduced parameters prove to be simple, convenient tools for examining data from plant adaptation trials in the presence of genotype x environment interaction.